DESIGN OF ELECTRONIC OPTICS AVTOEMISIYNIH MICROCATODIV - Голота, Віктор Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is analyzed field emission of semiconductors. Allocation of potentials and intensity of an electric field of field emission microcathodes are calculated by a method of finite differences. The design procedure of electrons motion trajectories in view of a spatial charge is developed.